In-situ kinetics of modifications induced by swift heavy ions in Al2O3: Colour centre formation, structural modification and amorphization. (November 2017) - Grygiel, C.; Moisy, F.; Sall, M.; Lebius, H.; Balanzat, E.; Madi, T.; Been, T.; Marie, D.; Monnet, I.
Abstract: This paper details in-situ studies of modifications induced by swift heavy ion irradiation in α-Al2O3. This complex behaviour is intermediary between the behaviour of amorphizable and non-amorphizable materials, respectively. A unique combination of irradiation experiments was performed at the IRRSUD beam line of the GANIL facility, with three different characterisation techniques: in-situ UV–Vis absorption, in-situ grazing incidence X-Ray diffraction and ex-situ transmission electron microscopy. This allows a complete study of point defects, and by depth profile of structural and microstructural modifications created on the trajectory of the incident ion. The α-Al2O3 crystals have been irradiated by 92 MeV Xenon and 74 MeV Krypton ions, the irradiation conditions have been chosen rather similar with an energy range where the ratio between electronic and nuclear stopping power changes dramatically as function of depth penetration. The main contribution of electronic excitation, above the threshold for track formation, is present beneath the surface to finally get almost only elastic collisions at the end of the projected range. Amorphization kinetics by the overlapping of multiple ion tracks is observed. In the crystalline matrix, long range strains, unit-cell swelling, local microstrain, domain size decrease, disordering of oxygen sublattice as well as colour centre formation are found. This study highlights the relationship between ion energy losses into a material and its response. While amorphization requires electronic stopping values above a certain threshold, point defects are predominantly induced by elastic collisions, while some structural modifications of the crystalline matrix, such as unit-cell swelling, are due to contribution of both electronic and nuclear processes. Graphical abstract: Image